Antiallergic effect of the alpha‐cyclodextrin Moringin complex in rat basophilic leukaemia (RBL‐2H3) cell line - Yousef A. Alnakeeb, Ebtisam; Abdull Razis, Ahmad Faizal; Wei Chan, Kim; Ling Tham, Chau; Han Chan, Yee; Kalifa Kafo, Anwar Salm; Jambari, Nuzul Noorahya; Rollin, Patrick; Djedaini-Pilard, Florence; Mutalik, Srinivas (Hindawi Limited, 2024)
Allergic diseases (ADs) are a major concern when it comes to public well-being. Moringa oleifera Lam is a tropical plant that is used in traditional medicine due to the presence of isothiocyanate. The present study investigated the antiallergic properties of 4-(α-L-rhamnopyranosyloxy)-benzyl isothiocyanate or moringin isolated from Moringa oleifera seeds in the form of alpha-cyclodextrin-moringin (α-CD/MG) complex on rat basophilic leukaemia (RBL-2H3) cell line at both the early and late stages of an allergic reaction. The α-CD/MG complex was initially elucidated using nuclear magnetic resonance (NMR) followed by the 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium inner salt proliferation assay to evaluate the cytotoxicity and cell viability with respect to ketotifen fumarate (KF) and α-CD/MG. The release of beta-hexosaminidase (β-hexosaminidase) and histamine was used to determine the level of inhibition in the early stage while the suppression of the release of prostaglandin (PGD2), tumour necrosis factor-alpha (TNF-α), and interleukin (IL-4) was considered in the late stage. Higher concentrations of α-CD/MG (5 μM, p<0.001) in mast cell degranulation significantly inhibited the expression of β-hexosaminidase, histamine, TNF-α, PGD2, and IL-4 in both the early and late stages. Thus, α-CD/MG can potentially be developed as an antiallergic drug as it has the ability to inhibit allergic responses in the late and early stages.